(untitled) (South East Asia Journal of Public Health, 2013)
In Bangladesh, the prevalence of low birth weight is unacceptably high. A cross sectional descriptive study was carried out during the period of June to September 2009 among the mothers whose babies were born in Bangladesh Medical College, a tertiary level hospital situated in Dhaka, to assess the proportion of children born with low birth weight. The mothers of 102 babies born within the specified period were chosen purposively for this study. A pre-tested structured questionnaire was used as the research instrument and data was collected from them by face to face interviews. Results revealed that the proportion of low birth weight babies was 25.49% (n-26). Most of the low birth weight babies (30.77%) identified came from families with an average monthly income of less than 5,000 Taka. Among 26 low birth weight babies, 21 (80.77%) were born before completing 37 weeks and only three (19.23%) were born after completing 37 weeks of the gestational period. Significant association was found between low birth weight babies and family income (p<0.001), and between low birth weight babies and pre-term (p<.0001). It is considered that the present findings of this study will not only help initiate measures to combat the problem in the future but also serve as a useful basis for research and planning. DOI: http://dx.doi.org/10.3329/seajph.v1i1.13209 South East Asia Journal of Public Health 2011:1:24-27